Assessing the impact of a tennis-themed sports video game on physical literacy and participation on physical activities among university students: A cluster randomized controlled trial study protocol - Wai Keung Ho; Raymond Kim Wai Sum; Siu Ming Choi (PLoS ONE, 2026)
Introduction Physical literacy (PL) is a multidimensional construct encompassing motivation, confidence, physical competence, knowledge, and understanding, which is essential for fostering lifelong physical activity. University students represent a critical stage for PL development, yet many experience a decline in physical activity and an increase in sedentary behavior after high school. Sports video games (SVGs), though traditionally sedentary, have shown potential to enhance motivation and cognitive engagement with sports. These games are especially popular among university students, making them an accessible and engaging tool for promoting PL. Despite their popularity, the role of SVGs in supporting PL development remains underexplored, particularly in Asian contexts. Integrating technology into physical education, such as through SVGs and virtual simulations, may offer innovative ways to enhance engagement and support PL development. Although the intervention is sedentary, SVG gameplay often requires reflexes and eye–hand coordination which may influence aspects of physical competence such as reaction time and coordination. This study aims to evaluate whether a tennis-themed SVG intervention integrated into PE lessons can enhance students’ motivation, sport-specific knowledge, physical competence, social engagement, and physical activity engagement, thereby promoting holistic PL development. Methods A cluster randomized controlled trial will be conducted with 176 first-year students enrolled in compulsory tennis physical education courses at The Chinese University of Hong Kong. Eight entire classes (four male and four female) will be randomly assigned to either an intervention or control group. The intervention group will play a tennis SVG, TopSpin 2K25, twice weekly for six weeks alongside regular PE lessons. Assessments at baseline, post-intervention, and three-week follow-up will include self-reported gaming behavior, physical activity level, PL domains, and objective tests of reaction time, eye-hand coordination, and tennis knowledge. Discussion This protocol examines the integration of SVG into physical education to promote PL across physical, cognitive, affective, and social domains. Limitations include potential contamination bias, variability in prior gaming experience, short intervention duration, and reliance on self-reported measures, which may introduce bias. Theoretically, the study advances PL frameworks by embedding technology-enhanced learning within structured PE contexts. Practically, SVG-based activities offer an inclusive, engaging approach to support diverse learners. Future research should explore long-term effects and develop validated tools for comprehensive assessment. Trial registration: The protocol has been registered on the Open Science Framework on 25 July 2025: https://doi.org/10.17605/OSF.IO/JDYGV .